2014
DOI: 10.1111/resp.12439
|View full text |Cite
|
Sign up to set email alerts
|

Repeated inhalation of sevoflurane inhibits airway inflammation in an OVA‐induced mouse model of allergic airway inflammation

Abstract: Background and objective: Repeated inhalation of sevoflurane (SVF) can benefit asthmatic patients by bronchodilation. However, the impact of repeated inhalation of SVF on allergic airway inflammation has not been clarified. This study was aimed at investigating the effects of repeated inhalation of SVF on airway inflammation in mice. Methods: Female C57BL/6 mice were sensitized with ovalbumin (OVA) and treated by inhalation with SVF or vehicle daily for seven consecutive days, immediately followed by OVA chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Other pathways have also been investigated and reported on in Respirology this year; sevoflurane, a volatile agent routinely used in anaesthesia, possesses anti‐inflammatory effects in animal models of acute lung injury. Shen et al found that repeated inhalation of sevoflurane inhibited allergic airway inflammation by reducing inflammatory cell infiltrates, modulating the imbalance of high‐mobility group box (HMGB) 1, tumour necrosis factor‐α and IL‐10 responses and mitigating allergen‐specific IgE responses and globlet cell hyperplasia in mice. HMGB1 is a non‐histone DNA‐binding nuclear protein acting as an endogenous ‘danger signal’, which triggers innate immune reactions .…”
Section: Asthmamentioning
confidence: 99%
“…Other pathways have also been investigated and reported on in Respirology this year; sevoflurane, a volatile agent routinely used in anaesthesia, possesses anti‐inflammatory effects in animal models of acute lung injury. Shen et al found that repeated inhalation of sevoflurane inhibited allergic airway inflammation by reducing inflammatory cell infiltrates, modulating the imbalance of high‐mobility group box (HMGB) 1, tumour necrosis factor‐α and IL‐10 responses and mitigating allergen‐specific IgE responses and globlet cell hyperplasia in mice. HMGB1 is a non‐histone DNA‐binding nuclear protein acting as an endogenous ‘danger signal’, which triggers innate immune reactions .…”
Section: Asthmamentioning
confidence: 99%
“…Previous studies have demonstrated that sevoflurane attenuated oleic acid-induced pulmonary oedema, decreased tumour nuclear factor- α , and ameliorated the alveolar damage score in dogs; sevoflurane was also shown to benefit patients with acute lung injury [ 26 , 27 ]. The results of previous studies in our laboratory show that the OVA-mediated increases in inflammatory cells around bronchi, goblet cell hyperplasia, and total numbers and differential counts of inflammatory cells in BALF were significantly inhibited by sevoflurane [ 13 ]. In accordance with the results of our colleagues, this study confirms the anti-inflammatory effects of sevoflurane, which is similar to MCC950.…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane, a commonly used volatile anaesthetic, has been used as a last-resort treatment for life-threatening asthma in children [ 9 ]. Apart from bronchodilation [ 10 – 12 ], our coworkers have confirmed that sevoflurane suppressed allergic airway inflammation by inhibiting inflammatory infiltrates and mucus production, as well as keeping balance of cytokine responses [ 13 ]. However, whether sevoflurane inhibits the Th2 response and NLRP3 inflammasome activation in allergic airway inflammation remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental research has demonstrated that inhalation of SVF may reduce inflammation in patients with ALI (28)(29)(30). SVF is a widely used anesthetic agent, and the protective effect of SVF under conditions of hypoxia or endotoxemia has been extensively studied (31).…”
Section: Discussionmentioning
confidence: 99%